The quercetin metabolite 4-methylcatechol causes vasodilation via voltage-gated potassium (KV) channels - Dias, Patrícia; Salam, Rudy; Pourová, Jana; Vopršalová, Marie; Konečný, Lukáš; Jirkovský, Eduard; Duintjer Tebbens, Jurjen; Mladěnka, Přemysl (Food & function, 2024)
Dietary polyphenols have been associated with many beneficial cardiovascular effects. However, these effects are rather attributed to small phenolic metabolites formed by the gut microbiota, which reach sufficient concentrations in systemic circulation. 4-Methylcatechol (4-MC) is one such metabolite. As it is shown to possess considerable vasorelaxant effects, this study aimed to unravel its mechanism of action. To this end, experimental in vitro and in silico approaches were employed. In the first step, isometric tension recordings were performed on rat aortic rings. 4-MC potentiated the effect of cyclic nucleotides, but the effect was not mediated by either soluble guanylyl cyclase (sGC), modification of cyclic adenosine monophosphate levels, or protein kinase G. Hence, downstream targets such as calcium or potassium channels were considered. Inhibition of voltage-gated K+ channels (KV) markedly decreased the effect of 4-MC, and vasodilation was partly decreased by inhibition of the KV7 isoform. Contrarily, other types of K+ channels or L-type Ca2+ channels were not involved. In silico reverse docking confirmed that 4-MC binds to KV7.4 through hydrogen bonding and hydrophobic interactions. In particular, it interacts with two crucial residues for KV7.4 activation: Trp242 and Phe246. In summary, our findings suggested that 4-MC exerts vasorelaxation by opening KV channels with the involvement of KV7.4.
Keywords: aorta; vazodilatace; draslíkové kanály řízené napětím; katecholy; Potassium Channels, Voltage-Gated; simulace molekulového dockingu; Vasodilation; vazodilatancia; Molecular Docking Simulation; krysa rodu Rattus; quercetin; zvířata; potkani Wistar; Catechols; Rats, Wistar; Male; Rats; Animals; Vasodilator Agents; mužské pohlaví; Aorta; Quercetin